Language, identity, and resistance to English hegemony: unpacking language ideologies in Twitter discourses on Twi usage among the ‘Kumasiano Guys’ in Ghana - Ernest Nyamekye; God’sgift Ogban Uwen (Cogent Arts & Humanities)
Despite the significant role of Twi as a means of communication and a tool for expressing the unique cultural identity of the Ashantis and other Akans, some Ghanaians misconstrue the preferential usage of Twi among the Kumasi people as indicative of limited English proficiency. This misconception often finds expression on platforms like Twitter, where Kumasi people are frequently subjected to ridicule for grammatical errors in English or for predominantly using Twi. This study, thus, explored the underlying ideologies shaping these Twitter discourses. A total of 56 tweets were analyzed using social media critical discourse analysis (SM-CDA). The study revealed a prevalent belief that Kumasi people’s reluctance to use English and their limited proficiency are indicative of low literacy and primitiveness. The counter-responses from the supposed Kumasi people, however, demonstrate a steadfast native language loyalty and a strong sense of Ashanti identity. Their responses further highlight the need for some Ghanaians to emancipate themselves from mental slavery, evident in their linguistic behaviors and attitudes. We, thus, conclude that the enduring affection for Twi and resistance to English usage among the Kumasi people and many Akans inadvertently contribute to the promotion of Akan/Twi expansionism over other indigenous languages.